Fauna e ecologia de endoparasitas de anuros do bioma Cerrado, nordeste do Brasil - SANTOS, Bárbara Rodrigues dos (2021)
The Brazilian Cerrado is one of the largest hotspots in the world, suffering of habitat and fragmentation loss and harboring endemic species of anurans. Anurans are hosts of a great endoparasites diversity, with which they establish important ecological relationships. However, the east of Maranhão, composed mostly by Cerrado, is a region with total scarcity of studies on anuran endoparasites. The aim of this study was to know the fauna and ecological aspects of endoparasites associated with 18 anurans species from the Cerrado do of east of Maranhão, Northeastern Brazil. Anurans were captured through active search, euthanized and analyzed for endoparasites. For the parasites, we calculated the quantitative descriptors, the STD* index of specificity and the Poulin Discrepancy Index. Using a Generalized Linear Mixed Model, we tested the influence of biological characteristics of hosts and parasites on the two indices and on the abundance of parasites. As a result, we found 12 taxa of endoparasites, 8 Nematoda, 3 Acanthocephala and 1 Cestoda. Physaloptera sp., Aplectana sp. and Rhabdias sp. were the most common nematodes in anuran taxocenosis, corroborating other studies that show these genera as dominant in the community. In particular, in addition to infecting 9 host species, Acanthocephala had a relatively high prevalence compared to work carried out in other localities. This may be associated with the diet of the hosts, since acanthocephalans depend on the ingestion of arthropods by anurans for their transmission. We also present 22 new records of hosts, expanding the knowledge about the endoparasite fauna of anurans in Brazil. The specificity index ranged from 1 to 3, where Oncicola sp. was the most specific parasite in the community. Heteroxenes parasites were more specific than monoxenes. This may reflect the parasites need to select suitable intermediate hosts, also resulting in a narrower range of definitive hosts. We also observed that the less specific the parasite, the greater its prevalence. This may be associated with the possibility of generalist parasites infecting hosts that are phylogenetically close and with immunological similarities to each other, reducing the costs of adaptation. In general, the parasites were spatially aggregated, but among the characteristics tested, none explained the levels found, indicating the action of other factors generating heterogeneity of exposure and susceptibility. Hosts with higher mass and CRC were more parasitized. The resources offered by larger frogs, as well as their diet and age, favor a greater parasite abundance. On the other hand, males had greater parasite abundance than females, indicating that physiological and ecological particularities of sex make males more susceptible and exposed to parasites.